Differences in Morphokinetic Parameters and Incidence of Multinucleations in Human Embryos of Genetically Normal, Abnormal and Euploid Embryos Leading to Clinical Pregnancy - Tvrdoňová, Kateřina; Belaskova, Silvie; Rumpikova, Tatana; Malenovska, Alice; Rumpik, David; Myslivcova Fucikova, Alena; Malir, Frantisek (Journal of clinical medicine, 2021)
The selection of the best embryo for embryo transfer (ET) is one of the most important steps in IVF (in vitro fertilisation) treatment. Preimplantation genetic testing (PGT) is an invasive method that can greatly facilitate the decision about the best embryo. An alternative way to select the embryo with the greatest implantation potential is by cultivation in a time-lapse system, which can offer several predictive factors. Non-invasive time-lapse monitoring can be used to select quality embryos with high implantation potential under stable culture conditions. The embryo for ET can then be selected based on the determined morphokinetic parameters and morphological features, which according to our results predict a higher implantation potential. This study included a total of 1027 morphologically high-quality embryos (552 normal and 475 abnormal PGT-tested embryos) from 296 patients (01/2016-06/2021). All embryos were cultivated in a time-lapse incubator and PGT biopsy of trophectoderm cells on D5 or D6 was performed. Significant differences were found in the morphological parameters cc2, t5 and tSB and the occurrence of multinucleations in the stage of two-cell and four-cell embryos between the group of genetically normal embryos and abnormal embryos. At the same time, significant differences in the morphological parameters cc2, t5 and tSB and the occurrence of multinucleations in the two-cell and four-cell embryo stage were found between the group of genetically normal embryos that led to clinical pregnancy after ET and the group of abnormal embryos. From the morphokinetic data found in the PGT-A group of normal embryos leading to clinical pregnancy, time intervals were determined based on statistical analysis, which should predict embryos with high implantation potential. Out of a total of 218 euploid embryos, which were transferred into the uterus after thawing (single frozen embryo transfer), clinical pregnancy was confirmed in 119 embryos (54.6%). Our results show that according to the morphokinetic parameters (cc2, t5, tSB) and the occurrence of multinucleations during the first two cell divisions, the best euploid embryo for ET can be selected with high probability.